(untitled) (Clinical Sociology Review, 2023)
Any inquiry into the condition of the churches to-day must consider the gulf existing between the church and the working class. We hardly realize, I think, that by a great section of the proletariat our religious organizations are regraded as the stronghold of hypocrisy and oppression. We hardly realize the bitterness that that these workers fell toward us as they repeat once again: “Woe unto you, scribes and Pharisees, hypocrites! for ye devour widows’ houses, and for a pretence make long prayers. Therefore, shall ye receive the greater damnation.”